Relationship Coping Mechanisms and Anxiety Levels in Patients Undergoing Chemotherapy at RSUP H. Adam Malik Medan 2024 - Rotua Elvina Pakpahan; Friska Sembiring; Naomi Rayani Simamora (NAJ Nursing Applied Journal, 2025)
Introduction Anxiety in chemotherapy patients who have just undergone chemotherapy has high anxiety due to ignorance and the side effects of chemotherapy that will be carried out and lack of knowledge. In this case, an Adaptive coping mechanism is needed to reduce the level of Anxiety in chemotherapy patients. The purpose of this study was to see the relationship between coping mechanisms and anxiety levels in patients undergoing chemotherapy. The research method uses a cross-sectional method design. The sample in this study uses a purposive sampling technique of 90 people. The measuring instrument uses the Ways of Coping questionnaire and the Halmilton Anxiety Rating Scale (HARS). The results showes that the coping mechanisms in respondents were more maladaptive coping mechanisms 66 people (73.3%), and severe anxiety levels 58 people (64.4%). Statistical test of the relationship between coping mechanisms and anxiety levels in patients undergoing chemotherapy using the Spearman rank test obtains a p value = 0.001, meaning that there is a relationship between coping mechanisms and anxiety levels in patients undergoing chemotherapy with a correlation coefficient value of -0.0841, a negative pattern relationship with very strong strength. Conclusion The researcher hopes that patients undergoing chemotherapy will get more sources of information related to their current illness, so that patients do not feel too anxious about their current illness.